Scholarship in nursing: Degree-prepared nurses versus diploma-prepared nurses - Lizeth Roets; Yvonne Botma; Cecilna Grobler (AOSIS, 2016)
Background: The nursing profession needs nurses with a higher level of education and not merely more nurses to enhance patient outcomes. To improve quality patient care the nursing discipline needs to be advanced through theory development and knowledge generation, thus graduate nurses. Nursing scholarship cannot be limited to nurse academics, but is the responsibility of every nurse. Although the world is looking towards combating the decline in nursing numbers with better educated nurses, South Africa is planning to address the problem with more lower qualified nurses. Aim: The aim of this study being reported here was to establish whether degree-prepared nurses in South-Africa partake more often in scholarly activities than diploma-prepared nurses. Method: A cross-sectional descriptive design was used. The population was all professional nurses registered with the South African Nursing Council who obtained either a four year degree or four year diploma in nursing. Data were gathered from 479 respondents, using a self-administrative questionnaire. Results: Three times more nursing educators (n = 19) achieved a degree as first qualification than their colleagues (n = 6) who achieved a diploma as first qualification. All but one (n = 18) nursing educators who obtained a degree as first qualification are educators in the private sector that include both universities as well as nursing colleges of private hospital groups. Data further revealed that most nurse educators and those in managerial positions were degree prepared. More degree prepared nurses than diploma prepared nurses were actively involved in scholarly activities such as research (30,5% compared to 25,5%) and implementing best practice guidelines (62,2% compared to 55,9%). Conclusion: The global nursing crisis, nor the nursing profession, will benefit by only training more nurses. The profession and the health care sector need more degree prepared nurses to improve scholarship in nursing.